MOBILIZING THE HALAL LIFESTYLE OF MIDDLE-CLASS MUSLIMS IN INDONESIA: AN ACCELERATION PROGRAM OF FREE HALAL CERTIFICATION FOR SMALL AND MICRO ENTERPRISES (SMES) - Putri Kamilatul Rohmi (UIN Kiai Haji Achmad Siddiq Jember, 2022)
The halal industry is now proliferating along with the halal lifestyle, which is very prominent in the Muslim middle class in Indonesia. The consequence is considered not only to have encouraged the development of the Islamic economy but also to intensify the halal lifestyle. This article discusses the government's acceleration of halal certification by accelerating the process of halal certification through the Free Halal Certification Program (Sehati) for Small and Micro Enterprises (SMEs). The program, especially food products, has accelerated the community's halal lifestyle, especially for middle-class Muslims in Indonesia. In doing so, the government contributes to mobilizing middle-class Muslim lifestyles in contemporary Indonesian culture.